Predictors of non-suicidal self-injury and moderating effects of cognitive emotion regulation strategies in Korean undergraduate students: Secondary data analysis of a cross-sectional survey - Yeo Won Jeong (PLoS ONE, 2026)
Background Non-suicidal self-injury (NSSI) is an emerging mental health issue in both clinical practice and public health worldwide, refers to intentional self-harm without suicidal intent. Exploring protective and moderating factors of NSSI is important for its prevention and intervention. However, most existing studies have focused primarily on risk factors. This study aimed to identify predictors of NSSI and examine the moderating effects of cognitive emotion regulation strategies on the relationship between psychological discomfort and NSSI. Methods This study involved a secondary analysis of data from 188 self-reported questionnaires collected via a web-based survey in South Korea between August and September 2020 during COVID-19 pandemic. NSSI was measured using the modified NSSI subscale of the Korean version of the Self-Harm Inventory. Psychological discomfort was assessed using a 20-item symptom checklist, and cognitive emotional regulation strategies were measured using the Cognitive Emotion Regulation Questionnaire. Data were analyzed using zero-inflated negative binomial regression. The Hayes PROCESS macro (Model 1) was used to examine moderating effects. Results Of the 188 participants, 159 were female. A total of 30.3% reported experiencing NSSI within the past six months. NSSI was associated with being female and lower use of positive cognitive emotion regulation strategies. Psychological discomfort was positively associated with NSSI. Positive cognitive emotion regulation strategies had a conditional moderating effect on the relationship between psychological discomfort and NSSI. However, negative cognitive emotion regulation strategies did not show a significant moderating effect. Conclusions Psychological discomfort is a salient risk factor for NSSI. Positive cognitive emotion regulation strategies may be an important protective factor. Therefore, prevention and intervention efforts should emphasize strengthening positive—rather than negative—cognitive emotion regulation strategies. To reduce NSSI among undergraduates with a history of NSSI, policies or psychoeducation should focus on increasing positive cognitive coping. Moreover, tailored interventions are needed to reduce psychological discomfort among students with no history of NSSI.